Factors influencing K-12 teachers’ experiences of using Generative AI Tools: opportunities and barriers - memnüne kokoç (Je-LKS: Journal of E-Learning and Knowledge Society)
Artificial intelligence (AI) teaching is becoming an increasingly popular topic among educators and researchers. Its importance in the research field stems from its ability to process and analyze large datasets, identify patterns and trends, provide new insights, and automate complex tasks. Educational policies make serious plans to develop teachers’ professional competencies and implement many in-service training. Concerns about the accuracy of the outputs produced by AI systems arise due to inaccuracies or biases that may be present in the data on which they are trained. The aim of the study was to identify teachers’ views on their digital skills in research studies using AI tools. In this study, a qualitative research method was used to find answers to the research questions. The data of the study were collected through a semi-structured interview form. The obtained data were analyzed with content analysis. The study group consisted of 14 (female=8; male=6) secondary school teachers. The findings of this study comprehensively examine the experiences of secondary school teachers using generative AI tools. The findings obtained in terms of opportunities and barriers reveal the importance of broad policy changes and supportive education programs to support the integration of technology in education. In addition, future expectations emphasize the need to strengthen the technological infrastructure and provide comprehensive training programs for teachers.